Effective Mg:Ag / MoO3 recombination zone for tandem organic photovoltaic devices. Issue 1737 (4th June 2015) - Jeong, A. R.; Wiesner, S.; Fengler, S.; Lux-Steiner, M. Ch.; Rusu, M.
ABSTRACT: We demonstrate an effective recombination zone consisting of Mg:Ag (1:3) alloy and MoO3 layers with 0.8 nm and 3 nm respectively for application in tandem organic photovoltaic devices based on zinc phthalocyanine (ZnPc) donor and fullerene C60 acceptor. The Mg:Ag layer ensures an optimum electron selectivity, while MoO3 layer effectively selects holes. A conversion efficiency of 2.2% has been achieved under an illumination of 100 mW/cm 2 at room temperature. The open circuit voltage of 810 mV is close to the sum of the open circuit voltages of the constituent single cells. The recombination Mg:Ag-MoO3 layer system is investigated with regard to the requirements of high optical transparency, work function compatibility, and facilitation of light absorption. The respective characterizations were carried out by UV-Visible spectroscopy, Kelvin probe force microscopy in ultrahigh vacuum, current-voltage and external quantum efficiency methods.